If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.9z+4.5=3.5z-3.3
We move all terms to the left:
0.9z+4.5-(3.5z-3.3)=0
We get rid of parentheses
0.9z-3.5z+3.3+4.5=0
We add all the numbers together, and all the variables
-2.6z+7.8=0
We move all terms containing z to the left, all other terms to the right
-2.6z=-7.8
z=-7.8/-2.6
z=3+-8.881784197E-16/2.6
| 2,5x+6=5x-2,1 | | n2=3.5 | | 3/4x+2x=26 | | 1.5x+9=3x-6 | | 9k-3k=0 | | 10=x-^2-8x1 | | 0.5x+9=3x-6 | | 18x=40(x-3)=468 | | 4v^2-5v+2=0 | | 10=j-6 | | -x-7+8x-5=8,5 | | 8t^2+9t+2=0 | | x^2+5x-6.25=0 | | 1/4=2/y | | 9x=x^2+x | | 2x+5=-39-5x | | -4(6+7x)=-192 | | 3.5x+4=6x-1 | | (100-y)+9=81 | | 2x=6=3x-8 | | 2=2/y | | 3(-2x-8=-24 | | (x-30)/5=-0.7 | | 2y+1÷3=y-1÷2 | | -4(-3x-5)=80 | | 3(2t+4)=10t-8 | | 1/3x=-6/1/6 | | 4=-2x=+26 | | -6(-6-7x)=498 | | 4(x=1)=3(x-2) | | 0.09=0.12*3.0/x | | 1/3x=-66/1 |